Housing affordability and housing policy in Urban China - Yang, Zan (SpringerBriefs in Economics, 2014)
This book provides a comprehensive analysis of housing affordability under the economic reforms and social transformations in urban China. It also offers an overall review of the current government measures on the housing market and affordable housing policies in China. By introducing a dynamic affordability approach and residual income approach, the book allows us to capture the size of the affordability gap more accurately, to better identify policy targets, and to assess the effectiveness of current public policy. The unique database on urban household surveys and regional information on affordable housing projects serve to strengthen the analysis. The book offers theoretical and empirical insights for in-depth affordability studies and helps readers to understand the social impacts of market reforms and the role of government on the Chinese housing market.